Changes in body composition parameters with duration in type II diabetics: an observational study - Raje, Leena; Mhaskar, Pallavi (International Journal Of Community Medicine And Public Health, 2020)
Background: Diabetes mellitus being a metabolic disorder lot of alteration takes place in body composition parameters such increase in fat mass, decrease in muscle mass, increase visceral fat. With advancing age, the predominant feature develops which is more prevalent in diabetes. These changes in body composition should be monitored. The changes if monitored at an early age, can be well managed and proper interventions can be developed. The study was conducted to observe the changes taking place in the body composition parameters in individuals with type II diabetes with varied duration of the disease. Methods: This cross- sectional study was done in 228 type II diabetic subjects from the clinics of the Mumbai and Pune. The baseline data was collected from the all the subjects coming to the clinic through the general questionnaire, Anthropometric measurements and Body composition analysis was done by the BIA principle-based Analyser. Then these subjects were distributed according to the duration of the disease and then analysed. The data was analysed using SPSS version 22 and mean values p values were obtained. Results: The results showed that there is statistically significant increase in fat mass, visceral fat and decrease in muscle mass. Conclusions: There is change in body composition parameters like decrease in muscle mass, increase in fat and visceral fat along with the increase in the duration of the disease.